Application of Feldspar Sand in Non-Autoclaved Foam Concrete Technology - Saduakassov, Mederbay; Lapin, Vladimir; Kopzhassarov, Bakhadyr; Tokmadzheshvili, Georgiy; Кushekov, Erlan; Ibraimbayeva, Gulnaz (Civil Engineering Journal, 2025)
The aim of this study is to determine the possibility of producing non-autoclaved foam concrete of grade M35 with a density of 900 kg/m³. A distinctive feature of this development is the testing of twin samples from the same batch: some were steamed in a chamber at 90 °C under normal atmospheric pressure, while others were autoclaved at a pressure of 8 bar and a temperature of 170 °C. It was established that ordinary natural feldspar sands with a fineness modulus ranging from 1.43 to 2.45, containing quartz below the standard-regulated levels, can be used in the production of non-autoclaved foam concrete. It is not possible to obtain non-autoclaved D900 foam concrete of grade M35 strength using only cement, sand, and foaming agent. To achieve the specified strength, it is necessary to use coarse sand with a fineness modulus (FM) greater than 3, subjected to short-term grinding to reduce the FM to recommended values, and to additionally introduce sol-gel liquid glass. The novelty lies in the experimental confirmation of the features of strength formation in cellular concrete under both non-autoclaved and autoclaved curing conditions. Comparative tests showed that high strength in cellular concrete is achieved only when a chemical bond forms between the products of cement hydrolysis and hydration with quartz sand grains—conditions made possible through autoclaving.